Horae homileticae: or Discourses, now first digested into one continued series, and forming a commentary upon every book of the Old and New Testament, to which is annexed an improved edition of a translation of Claude's Essay on the composition of a sermon - Simeon, Charles (Holdsworth, 1832)
Vol. 1. Genesis to Leviticus.- Vol. 2. Numbers to Joshua.- Vol. 3. Judges to Second Book of Kings.- Vol. 4. First of Chronicles to Job.- Vol. 5. Psalms I-LXXII.- Vol. 6. Psalms, LXXIII-CL.- Vol. 7. Proverbs to Isaiah XXVI.- Vol. 8. Isaiah XXVII-LXVI.- Vol. 9. Jeremiah to Daniel.- Vol. 10. Hosea to Malachi.- Vol. 11. Matthew.- Vol. 12. Mark to Luke XVI.- Vol. 13. Luke XVII to John XII.- Vol. 14. John XIII to Acts.- Vol. 15. Romans.- Vol. 16. 1st and 2nd Corinthians.- Vol. 17. Galatians. Ephesians.- Vol. 18. Philippians to 1 Timothy.- Vol. 19. 2 Timothy to Hebrews.- Vol. 20. James to Jude.- Vol. 21. Revelation. Claude's Essay. Indexes.